2020
DOI: 10.1007/s10068-020-00758-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of E. coli O157:H7 by a novel access with combination of improved sample preparation and real-time PCR

Abstract: Foodborne bacteria are typically present at very low concentrations in food. This study describes a quick and simple method for concentrating E. coli O157:H7 present in lettuce and cabbage, without microbial enrichment culture. This method involved reducing the extraction buffer and DNA elution volumes. The extraction buffer volume was adjusted to 225, 100, 50, 25, and 12.5 mL to isolate E. coli O157:H7 from 25 g of lettuce or cabbage. DNA was concentrated and compared using real-time PCR. When using 12.5 mL o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Due to the fact that the ICP::fusion system bypasses host-TXTL and is constrained only by the time taken for the phage to adsorb to their host, it is expected that it has the potential to vastly outperform existing phage-based approaches, and potentially rival the fastest E. coli detection system that has been published [10]. However, for the ICP::fusion system to be able to match the sub-10 CFU/mL LoD displayed in state-of-the-art E. coli detection systems [7][8][9][10], it is expected that significant optimisations will need to be made.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that the ICP::fusion system bypasses host-TXTL and is constrained only by the time taken for the phage to adsorb to their host, it is expected that it has the potential to vastly outperform existing phage-based approaches, and potentially rival the fastest E. coli detection system that has been published [10]. However, for the ICP::fusion system to be able to match the sub-10 CFU/mL LoD displayed in state-of-the-art E. coli detection systems [7][8][9][10], it is expected that significant optimisations will need to be made.…”
Section: Discussionmentioning
confidence: 99%
“…This review revealed that the application of PCR-based methods for foodborne pathogen detection in food samples is widespread, likely due to their relative sensitivity, specificity, reliability, reproducibility, rapid analysis, and wide applicability compared to traditional culture-based techniques. Thus far, PCR-based methods have been demonstrated as the most mature amplification methods that allow for simultaneous detection of multiple pathogens in a single reaction ( Kim and Oh, 2020b , Wei et al, 2019 ). In the current state, however, PCR-based methods are unsuitable for on-site detection due to their reliance on complex sample preparation and purification as well as complex thermal cycling devices.…”
Section: Remaining Challenges and Possible Opportunitiesmentioning
confidence: 99%
“…aureus in cherry tomato, milk, and spam, and reported 3 log CFU/ (g or ml) of detection limit. Kim and Oh (2020) applied PCR analysis to detect E . coli O157:H7 in lettuce and cabbage, and indicated that reducing the volume of DNA extraction and elution buffer increased the detection sensitivity.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%